2017
DOI: 10.1002/zaac.201700297
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hybrid Tin Halide Perovskite Solar Cells with Less Hazardous Solvents: Methanol and 1,4‐Dioxane

Abstract: Abstract. The toxicity of lead and the solvents utilized during the synthesis of hybrid halide perovskite films are potential obstacles for widespread applications of solar cell technology based on these materials. Alternatives such as those based on lead-free Sn-based devices often suffer from poor film morphologies, thus precluding competitive device efficiencies. Herein, we demonstrate a new one-step route deploying mixtures of the less hazardous methanol and 1,4-dioxane for preparing high-quality methylamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Despite an increment in the device stability, the efficiency was limited to values ≈2% due to the high background hole density of the MASnI 3 compounds. [ 174,200,216,217 ]…”
Section: Solar Cellsmentioning
confidence: 99%
“…Despite an increment in the device stability, the efficiency was limited to values ≈2% due to the high background hole density of the MASnI 3 compounds. [ 174,200,216,217 ]…”
Section: Solar Cellsmentioning
confidence: 99%
“…Sn‐based perovskites have a low value of V oc mainly because of the high defect density on which Greul et al suggested using the mixture of methanol and 1,4‐dioxane as the solvents whose toxicity are quite less than DMF and DMSO . A surprisingly low defect density was achieved for the MASnBr 0.5 I 2.5 films using methanol/dioxane, and the developed device showed an enhanced PCE of 1.05% and J sc of 15.44 mA cm −2 , whereas the cells grown through DMF exhibited PCE 0.04% and through DMSO exhibited PCE 0.01%.…”
Section: Sn‐based Perovskite Solar Cell Materialsmentioning
confidence: 99%
“…demonstrated the fabrication of MASnI 3 and MASnBr x I 3‐x films with high quality using a green solvent, a mixture of methanol and 1,4‐dioxane. [ 52 ] The MASnBr 0.5 I 2.5 solar cells fabricated through the methanol/dioxane procedure achieved PCE of 1.05% and J sc of 15.44 mAcm −2 .…”
Section: Sn‐based Perovskite Solar Cellsmentioning
confidence: 99%